2017
DOI: 10.1182/bloodadvances.2016003384
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin dynamics during the differentiation of long-term hematopoietic stem cells to multipotent progenitors

Abstract: Key Points ATAC-seq provides genome-wide chromatin state in 3 cell types of hematopoietic stem/progenitor cells. Transcription factor cohorts are associated with dynamic changes of open chromatin during the differentiation of LT/ST-HSCs to MPPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…Given the transcription-dependent incorporation mode of H3.3 (Ahmad & Henikoff, 2002b, Tagami et al, 2004, it is possible that this biased H3.3 inheritance contributes to or correlates with higher transcriptional activities in GSCs compared to CBs. These results are consistent with previous reports that stem cells maintain an overall more open chromatin state and their differentiated cells begin to "lock down" their chromatin towards a more restricted cell fate (Gaspar-Maia, Alajem et al, 2011, Golkaram, Jang et al, 2017, Turner, 2008, Yu, Wu et al, 2017).…”
Section: Dividing Female Gscs and Cbs Show Globally Symmetric But Locsupporting
confidence: 92%
“…Given the transcription-dependent incorporation mode of H3.3 (Ahmad & Henikoff, 2002b, Tagami et al, 2004, it is possible that this biased H3.3 inheritance contributes to or correlates with higher transcriptional activities in GSCs compared to CBs. These results are consistent with previous reports that stem cells maintain an overall more open chromatin state and their differentiated cells begin to "lock down" their chromatin towards a more restricted cell fate (Gaspar-Maia, Alajem et al, 2011, Golkaram, Jang et al, 2017, Turner, 2008, Yu, Wu et al, 2017).…”
Section: Dividing Female Gscs and Cbs Show Globally Symmetric But Locsupporting
confidence: 92%
“…4F ). Apart from an AT-rich motif in both clusters, the cell type-specific cluster 1 peaks were significantly enriched for Elf5 and Runx1 motifs, which are TFs involved in HSC differentiation ( 13 , 34 ). In cluster 2, we found motifs for the known erythroid regulators Gata1 and Arid3a ( 35 , 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, long-term HSCs (LT-HSCs) display increased number of assay of transposase accessible chromatin sequencing (ATAC-seq) peaks when compared to short-term HSCs ( 13 ) and high levels of histone H4K16ac ( 14 ), which is known for directly affecting chromatin accessibility in vitro ( 15 ). Nevertheless, several questions remained unanswered: What factors control these global chromatin accessibility changes?…”
Section: Introductionmentioning
confidence: 99%
“…One such study, carried out in human T-helper cells, found that genes with accessible promoters and high expression were enriched for housekeeping functions, whereas those with inaccessible promoters were enriched for olfactory terms [27]. A more recent study also found that genes with accessible promoters in three different types of hematopoietic stem cells (HSCs) were enriched for terms related to regulating the cell cycle and DNA damage and repair [28].
Fig.
…”
Section: Resultsmentioning
confidence: 99%